PENGOLAHAN RUMPUT LAUT MENJADI PUDING DI DESA KAYANG KECAMATAN PANTAR BARAT LAUT - Rudi K.Lema Killa; Simson Amung, Sulmiaty S. Sulaiman, Lucinia Wulandari Pen Duka, Lusia Lapaibuil, Finson Lauata, Dork (Adiba Aisha Amira, 2025)
The 2025 KBPM at Tribuana University Kalabahi is implemented with an empowerment paradigm, carrying the theme: 'KBPM Tribuana University Kalabahi: Impacting from Villages to the Global Market; Transforming Superior Village Products.’’' One of the KBPM Tribuana University Kalabahi locations is in Kayang Village, Pantar Northwest District. Kayang Village has seaweed potential with many benefits, one of which is as a food ingredient. Seaweed pudding is tangible proof of culinary creativity in the village's superior products, which is not only delicious but also rich in benefits. This pudding is not just an ordinary snack but a perfect combination of soft, chewy texture and the right sweetness.Through training and pudding production, this becomes a new skill in managing home industries, practical and low-cost. The ease of sustainable production is due to the sufficient availability of raw materials (seaweed). As for marketing prospects, it is well understood that market access and demand must continuously be improved by implementing efficient and effective promotional strategies, packaging design, and utilizing social media to expand market networks. The sustainability of seaweed development businesses must receive serious attention from the Kayang village government by encouraging village-level PPK by developing pudding businesses as one of the small home industries to gain economic profits.